PELATIHAN PEMBUATAN HAND SANITIZER ALAMI BERBASIS MINYAK KAYU PUTIH DI DESA PASSO, KECAMATAN BAGUALA, KOTA AMBON - Grace Sipahelut, Sophia; Novalin Lawalata, Vita; Lumbang Tobing, Marchel (HIRONO : Jurnal Pengabdian Masyarakat, 2021)
This activity is a community service activity that aimed to increase the knowledge and skills in making eucalyptus oil-based hand sanitizers in Passo Village, Teluk Ambon Baguala District, Ambon City. The target of this activity is the people of Passo Village, while the methods used are counseling and training. This activity went well and smoothly and provided benefits for the people of Passo Village, Baguala District, Ambon City. Participation of participants in this activity was also good, as seen from the enthusiasm of participants in participating in this activity ranging from counseling activities to training. Through outreach activities, the community gains knowledge and knowledge about the content of eucalyptus oil and its use, advantages and disadvantages of hand sanitizers, simple technology for making hand sanitizers made from natural eucalyptus oil. People understand more about the importance of making hand sanitizers made from natural ingredients. Implementation and practice that can improve people's skills in making hand sanitizers with the addition of eucalyptus oil as a substitute for alcohol